Antimicrobial properties of serum from captive Estuarine Crocodile (Crocodylus porosus) and False Gharial (Tomistoma schlegelii) - Ishak, Adilah (2018)
The serum of Estuarine Crocodile (Crocodylus porosus) and False Gharial (Tomistoma schlegelii) were known to have antimicrobial properties. This allows crocodiles to live in harsh and highly pathogenic environment without the threat of being fatally infected. A study on serum from captive Estuarine Crocodile and False Gharial was conducted to examine the antimicrobial properties. Blood samples from 2 Estuarine Crocodiles and 2 False Gharials were collected from the dorsal tail vein by using a 5 inch 18 G needle of 10 ml syringe. The blood was left to clot and centrifuged. The serum samples of Estuarine Crocodile and False Gharial were collected to determine the antimicrobial properties against 6 pathogenic bacteria by performing disc diffusion method and observation of inhibitory zone on Mueller Hinton agar. The zone of inhibition was examined, measured, recorded and analysed after 24 hours of agar incubation at 37oC. The results showed no antimicrobial properties against Escherichia coli, Salmonella sp, Staphylococcus aureus, Klebsiella pneumoniae, Enterobacter cloacae and Pseudomonas aeruginosa. In conclusion, there are no antimicrobial properties in serum from captive Estuarine Crocodile and False Gharial in this particular study.